1992
DOI: 10.1021/ic00041a005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and preliminary photophysical studies of intramolecular electron transfer in crown-linked donor- (chromophore-) acceptor complexes

Abstract: Among the emerging themes in chemical, biological, and photosynthetic studies of electron-transfer (ET) reactivity is the apparently essential role played by superexchange and related phenomena in facilitating long-range donor-acceptor coupling.1 Indeed, numerous recent model studies2•3 have emphasized the importance of the intervening medium-typically a covalently bound bridge-in providing energetically accessible virtual states or "conduction" pathways. Often, however, in naturally occurring ET processes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…One possible mechanism for this deactivation pathway is reductive quenching by the deprotonated hydroxypyridine ligand. Intramolecular electron transfer reactions in the excited state are well known, [7][8][9][10] and it is clear that the reducing power of the hydroxypyridine ligand will be enhanced by deprotonation. This is supported by the observed differences in quenching between phenol and phenolate, which correlates well with the difference in reduction potentials of approximately 200 mV.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism for this deactivation pathway is reductive quenching by the deprotonated hydroxypyridine ligand. Intramolecular electron transfer reactions in the excited state are well known, [7][8][9][10] and it is clear that the reducing power of the hydroxypyridine ligand will be enhanced by deprotonation. This is supported by the observed differences in quenching between phenol and phenolate, which correlates well with the difference in reduction potentials of approximately 200 mV.…”
Section: Discussionmentioning
confidence: 99%
“…The transition metal complexes have been investigated, and many of them have shown that they might be utilized in electron transfer studies, solar energy conversion and catalysis . Possible applications as luminescent sensors, molecular materials for nonlinear optics or optical switching have also emerged. In particular, luminescent transition metal complexes of Re(I) and Ru(II) with polypyridil ligands have been recognized as good potential candidates for the development of pH sensing devices .…”
Section: Introductionmentioning
confidence: 99%
“…5 upon nestling in the central cavity. 43 The reasons for this effect is currently unknown. More detailed examination of guest-induced spectral shifts and lifetime effects in this family would be welcome from a sensor perspective.…”
Section: Fig4 Spaced Type Macrocyclic Fluorescent Compounds With Ict Excited Statesmentioning
confidence: 99%